PERANAN KETELADANAN ORANG TUA DALAM MEMBENTUK KEPRIBADIAN DAN AKHLAK ANAK DI SDN CIBULUH 02 BOGOR UTARA - Kadir, Amalliah (Prodi PAI IAILM Suryalaya, 2018)
This research was conducted to examine more deeply the role ofparents in shaping personality, morals and any factors that becomeobstacles and supporters in shaping children's personality and moralsin SDN 02 Cibuluh Bogor Utara. It is a qualitative research with datacollection methods (observation, interview, documentation), thenanalyzed using descriptive methods (by recording and reviewing allresults of data obtained from various sources, case studies, comparativestudies, time and motion studies, behavior analysis) and the object ofthis research was chosen by purposive sampling method. The results ofthis study get clarity that the importance of the role of parents inshaping personality, including: good time management, smile,greetings, and familiarize good behaviour. The role of parents inshaping morality includes: always remember to die, fear of Allah,always reminding that everything we have can not be taken into theafterlife-world except our valuable knowledge that we had done in life,shadaqah jariyah, and the prayer of the good children. The importantrole of parents is as the child companion, as a preacher and qudwahhasanah (good role model), controller, motivator, mediator, technicalmanager of children in every process of child development, especiallyin aspects of personality and morals.